Consumer Perception of “Preloved” Luxury Apparels/Accessories in the Malaysian Context - Shaari, Noor Shakila (2013)
The research examined the effect of a few groups of variables on purchase intention of “preloved” luxury fashion designer brands. Data of 400 consumers based in Malaysia were gathered for this study. Survey question was administered via mass mailing of email to friends and colleagues and response was collected and analysed using Statistical Package for Social Science in short SPSS. Analysis result shows that consumer involvement and confidence does indeed affect purchase intention. Results of SPSS analysis also indicated that monthly income and age does not moderate the interactions for purchase intentions. As for most research, the sample population was not large and diverse enough to fully represent the entire population. Hence there is still room for improvement.